Influence of post-fixation time on shear bond strength of brackets fixed with different bonding materials (Pesquisa Odontológica Brasileira, 2002)
The purpose of this study was to evaluate the shear bond strength of four bonding materials for brackets, 10 minutes and 24 hours after their fixation, as well as the kinds of fracture observed. The buccal surfaces of 32 premolars were etched for 30 seconds with 35% phosphoric acid, and brackets were bonded using Orthodontic Concise (3M) and Z100 (3M). In other 32 premolars, brackets were bonded with Fuji I (GC) and Fuji Ortho LC (GC) on the buccal surfaces, without acid etching. After the bonding procedures, 32 samples were stored in distilled water at 37ºC for 10 minutes, and 32 samples were stored at the same temperature for 24 hours. The samples were then submitted to shear bond strength testing in an Instron testing machine, at a crosshead speed of 0.5 mm/min. The results were submitted to ANOVA and Tukeys test (p < 0.05). The results indicated that, for 10 minutes and 24 hours, Orthodontic Concise showed shear bond strength values (6.22 and 7.73 MPa, respectively) higher than Fuji Ortho LC (3.32 and 5.10 MPa), Z100 (2.72 and 4.51 MPa) and Fuji I (2.52 and 4.54 MPa). No statistical difference was verified between Fuji Ortho LC, Z100 and Fuji I (p < 0.05). In conclusion, Orthodontic Concise showed better shear bond strength values than the other three bonding materials, for both 10-minute and 24-hour storage periods; the shear bond strength averages were higher for the storage time of 24 hours, for all tested materials, and a great number of adhesive fractures were observed in the specimens which received Fuji I, Orthodontic Concise and Z100.